2002
DOI: 10.1152/ajplung.00296.2001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of IL-13 on airway responses in the guinea pig

Abstract: .-Levels of interleukin (IL)-13 are increased in asthmatic airways. IL-13 has been shown to be necessary and sufficient for allergen-induced airway hyperresponsiveness and increased inflammatory cell counts in bronchoalveolar lavage (BAL) fluid in a murine model of asthma but is thought to protect against airway inflammation when low doses are provided to the guinea pig lung. To determine the role of IL-13 in the guinea pig, we studied the effects of a 360-g/kg dose of nebulized IL-13 in naive animals and of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 28 publications
1
14
0
1
Order By: Relevance
“…IL-13 gene-deleted mice fail to develop allergen-induced AHR (30), and the inhibition of IL-13 through the administration of a soluble form of the IL-13 receptor (IL-13R␣ 2 ) reverses OVA-induced AHR in mice (31) and guinea pigs (20). In the current study, a neutralizing antibody directed against IL-13 also inhibited the development of AHR after OVA challenge.…”
Section: Discussionmentioning
confidence: 48%
“…IL-13 gene-deleted mice fail to develop allergen-induced AHR (30), and the inhibition of IL-13 through the administration of a soluble form of the IL-13 receptor (IL-13R␣ 2 ) reverses OVA-induced AHR in mice (31) and guinea pigs (20). In the current study, a neutralizing antibody directed against IL-13 also inhibited the development of AHR after OVA challenge.…”
Section: Discussionmentioning
confidence: 48%
“…8,9 Similarly, we have shown that intratracheal instillation of mIL-13 induced IgE, pulmonary eosinophilia, mucus production and AHR. 8,9,16 In this study, we have extended our analysis of this model using microarray expression profiling and have identified genes uniquely associated with IL-13 activity and antagonism. In addition, we have demonstrated a substantial overlap in gene expression changes following OVA challenge and intratracheal instillation of IL-13.…”
Section: Discussionmentioning
confidence: 99%
“…It is actively secreted during the late asthmatic response in mild asthmatic subjects (16) and has been implicated in the development of airway hyperresponsiveness (AHR) in models of allergic asthma. IL-13-genedeleted mice fail to develop allergen-induced AHR (32), and the inhibition of IL-13 through the administration of the soluble IL-13 receptor (IL-13R␣2) reverses ovalbumin-induced AHR in mice (33) and guinea pigs (23). Repeated administration of IL-13 to naïve mice and the overexpression of IL-13 by murine airway epithelium cause AHR (33,38).…”
mentioning
confidence: 99%
“…Repeated administration of IL-13 to naïve mice and the overexpression of IL-13 by murine airway epithelium cause AHR (33,38). Although IL-13 promotes inflammation, AHR is rapidly induced by the administration of IL-13 to experimental animals and precedes inflammation (23,31).…”
mentioning
confidence: 99%